Effects of Germinated Soybean on Serum Lipids in Rats - Mesomya, Wanpen; Cuptapun, Yaovadee; Hengsawadi, Duangchan; Lohana, Saruda; Yaieiam, Sompoch (Pakistan Journal of Nutrition, 2013)
The purpose of this research was to evaluate the effects of germinated soybean on serum lipids by feeding male Sprague-Dawley rats with 6 experimental diets containing 10% protein-casein (control), 10% protein- soy protein isolate (10% SPI), 10% protein-ungerminated soybean (10% UGS), 10% protein- germinated soybean (10% GS), 20% protein-germinated soybean (20% GS) and 28% protein-germinated soybean (28% GS). The diets were prepared from 6 formulas by AOAC, with the following composition:10%, 20% and 28% test protein, 8% oil, 5% water, 5% AIN-mineral, 1% AIN-vitamin, 1% cellulose, 35% sucrose and 35% corn starch. The results showed that serum cholesterol, triglyceride, HDL-c and LDL-c levels were not significantly different among the rats fed with 10% UGS and 10% GS diets. However, serum cholesterol, triglyceride and LDL-c level in rats fed with 20% GS and 28% GS diets were significantly lower than those in rats fed with 10% UGS and 10% GS diets. Serum cholesterol, triglyceride and LDL-c levels in rats fed with 28% GS diet (57.40±6.25, 30.30±5.25,11.80±2.69 mg/dL) were significantly lower than those in rats fed with SPI diet (73.10±13.32, 58.20±13.13, 23.40±5.01 mg/dL). The data indicated that the experimental diet with 28% protein-germinated soybean could reduce serum cholesterol, triglyceride and LDL-c in the experimental rats.